Clinical use of the co‐formulation of insulin degludec and insulin aspart. Issue 8 (7th July 2016) - Kumar, A.; Awata, T.; Bain, S. C.; Ceriello, A.; Fulcher, G. R.; Unnikrishnan, A. G.; Arechavaleta, R.; Gonzalez‐Gálvez, G.; Hirose, T.; Home, P. D.; Kaku, K.; Litwak, L.; et al.
Summary: Aims: To provide a review of the available data and practical use of insulin degludec with insulin aspart (IDegAsp). Premixed insulins provide basal and prandial glucose control; however, they have an intermediate‐acting prandial insulin component and do not provide as effective basal coverage as true long‐acting insulins, owing to the physicochemical incompatibility of their individual components, coupled with the inflexibility of adjustment. The molecular structure of the co‐formulation of IDegAsp, a novel insulin preparation, allows these two molecules to coexist without affecting their individual pharmacodynamic profiles. Methods: Clinical evidence in phase 2/3 trials of IDegAsp efficacy and safety in type 1 and type 2 diabetes mellitus (T1DM and T2DM) have been assessed and summarised. Results: In people with T2DM, once‐ and twice‐daily dosing provides similar overall glycaemic control (HbA1c ) to current modern insulins, but with lower risk of nocturnal hypoglycaemia. In prior insulin users, glycaemic control was achieved with lower or equal insulin doses vs. other basal+meal‐time or premix insulin regimens. In insulin‐naïve patients with T2DM, IDegAsp can be started once or twice‐daily, based on individual need. People switching from more than once‐daily basal or premix insulin therapy can be converted unit‐to‐unit to once‐daily IDegAsp, although this strategy should be assessed by the physician on an individual basis. Conclusions: IDegAsp offers physicians and people with T2DM a simpler insulin regimen than other available basal‐bolus or premix‐based insulin regimens, with stable daytime basal coverage, a lower rate of hypoglycaemia and some flexibility in injection timing compared with premix insulins.